Metformin encapsulated gold nanoparticles (MTF‐GNPs): A promising antiglycation agent. (13th September 2022) - Alenazi, Fahaad; Saleem, Mohd; Khaja, Azharuddin Sajid Syed; Zafar, Mubashir; Alharbi, Mohammed Salem; Hagbani, Turki Al; Ashraf, Jalaluddin Mohammad; Qamar, Mohammad; Rafi, Zeeshan; Ahmad, Saheem
Abstract: The generation of advanced glycation end products (AGEs) through nonenzymatic protein glycation contributes to the pathogenesis of long‐lived diabetic problems. Metformin (MTF) is the very first drug having antihyperglycemic effects on type II diabetes mellitus which also possess interaction with dicarbonyl compounds and blocks the formation of AGEs. In the current study, MTF is bioconjugated with glycation‐derived synthesized gold nanoparticles (GNPs) of significant size. Additionally, using various biophysical and biochemical approaches, we investigated the antiglycating capacity MTF‐GNPs in contrast to MTF against d ‐ribose‐derived glycation of bovine serum albumin. Our key findings via utilizing various assays demonstrated that MTF‐GNPs were able to inhibit AGEs development by reducing hyperchromicity, early glycation products, carbonyl content, hydxoxymethylfurfural content, production of fluorescent AGEs, normalizing the loss of secondary structure (i.e., α‐helix and β‐sheets) of proteins, elevating the levels of free lysine and free arginine more efficiently compared to pure MTF. Based on these results, we concluded that MTF‐GNPs possess a considerable antiglycation property and may be developed as an outstanding anti‐AGEs treatment drug. Further in vivo and clinical research are necessary to determine the therapeutic effects of MTF‐GNPs against AGE‐related and metabolic disorders. Highlights: Metformin is the first drug which interacts with dicarbonyl compounds and blocks the formation of AGEs. Metformin is bioconjugated with glycation‐derived synthesized gold nanoparticles (GNPs) of significant size. MTF‐GNPs were able to inhibit AGEs development by reducing hyperchromicity, early glycation products (EGEPs), carbonyl (CC), and Hydxoxymethylfurfural (HMF) content etc. MTF‐GNPs possess a considerable anti‐glycation property and may be developed as an outstanding anti‐AGEs treatment drug. Significance The key concluding of the current research demonstrates that the efficacy of the metformin (MTF) is enhanced by bioconjugating it with gold nanoparticles (MTF‐GNPs). Our findings also depict that MTF‐GNPs have higher antiglycation activity (utilized at lower doses) in contrast to the pure metformin antiglycation drug (utilized at higher doses, responsible for causing side‐effects in an individual). Therefore, MTF‐GNPs can be utilized as a promising anti‐AGE therapeutic drug (possessing high effectiveness and lower side effects) and, perhaps, diabetic problems in the future.